The Effects of Fenobucarb on the Physiology, Behavior, and Growth of Silver Barb (Barbonymus gonionotus) - Tam Thanh Nguyen; Håkan Berg; Loi Ngoc Nguyen; Yen Thi Hai Nguyen; Cong Van Nguyen (Toxics)
This study assessed the effects of fenobucarb (F) (1%, 10%, and 20% of the LC50-96h value) on the brain cholinesterase (AChE) activity, food intake (FI), feed conversion rate (FCR), and growth of silver barb (Barbonymus gonionotus, Bleeker, 1849). It also assessed the AChE inhibition levels that cause the abnormal swimming, behavior, and mortality of silver barb and how the feeding regime affects the recovery rate of the AChE activity. The results showed that the brain AChE inhibition increased with the F concentrations. It peaked after nine hours, at 73.6% and 79.7% for the two highest concentrations, and then the AChE activity started to recover. After 96 h, the inhibition level was still 11.8% in the fish exposed to the two lowest concentrations and 30.5% in the fish exposed to the highest concentrations. Even when placed in clean water, the inhibition level in the fish that were exposed to the highest concentrations and only fed every third day was 32% after 14 days. Although there were no differences in the feed intake at any time, the fish exposed to F had a higher FCR and a lower specific growth rate and weight compared to the control fish at the later stages of the experiment. Thus, although the use of F in rice farming in the Mekong Delta may not lead to direct fish kills, it impacts the growth and health of the fish, which could have negative implications for wild fish populations and the long-term production of healthy fish in the Mekong Delta.